Effect of comprehensive, individualized, person‐centered management on antidepressant usage in advanced Alzheimer's persons in a 28‐week, randomized, controlled trial: Dementia care research (research projects; nonpharmacological)/Therapeutic strategies and interventions. (7th December 2020) - Kenowsky, Sunnie; Shao, Yongzhao; Torossian, Carol; Saad, Muhammad; Dafflisio, Gianna; Vedvyas, Alok; Reisberg, Barry
Abstract: Background: We published results of a clinician‐blind, parallel‐group study of Comprehensive, Individualized, Person‐Centered Management (CI‐PCM) in moderate‐to‐severe, community‐residing, Alzheimer's persons (Reisberg…Kenowsky, Dement Geriatr Cogn Disord, 2017). CI‐PCM intervention subjects (n=10) showed 967% greater global improvement than subjects randomized to Usual Community Care (UCC, n=10). Behavioral Pathology in Alzheimer's Disease‐Frequency Weighted (BEHAVE‐AD‐FW) total scores showed significant benefit in the intervention group at week 28 (p<0.05). Kettunen asserts, (Eur J Clin Pharmacol, 2018), "Among persons with AD, antidepressants are used for treatment of BPSD…their effectiveness in this indication is modest." Casey states, (Pharmacy & Therapeutics, 2015), "Antidepressants…are widely used in dementia for depressed mood, anxiety, agitation, and apathy." Bui recommends, (Cochrane for Clinicians, American Family Practice, 2012), "…antidepressants should be used [in patients with dementia] only if all other nonpharmacologic interventions for neuropsychiatric symptoms are unsuccessful." Herein, we examine the effect of the CIPCM program on antidepressant usage and the Behavioral and Psychological Symptoms of Dementia (BPSD) as measured with the BEHAVE‐AD‐FW. Method: Investigators blinded to treatment group assignment reviewed subject charts (N=20), for antidepressant usage, and BEHAVE‐AD‐FW total and category F scores, which measure tearfulness and depressed mood. Costs of antidepressant usage, and BEHAVE‐AD‐FW total, and category F scores for each group were compared. Result: There were no significant differences in antidepressant usage or BEHAVE‐AD‐FW total or category F scores between groups at baseline. At all study visits, 50% of subjects in each group took antidepressants. At week 28, community physicians prescribed CI‐PCM subjects less or the same dose of antidepressants, and prescribed comparator subjects the same or greater doses, and additional antidepressants. BEHAVE‐AD‐FW category F scores for UCC comparators were persistently elevated and worsened by week 28, whereas, CI‐PCM group scores improved to zero, indicating no depressive symptoms. Conclusion: For CI‐PCM subjects, total BPSD symptomatology declined significantly (p<0.05), antidepressant usage declined, and tearfulness and depressed mood resolved, by week 28. In contrast, UCC subjects increased antidepressant usage, paid 4.42 times more for antidepressants, and had worsening of behavioral disturbances and depressive symptoms. CI‐PCM is an effective nonpharmacologic intervention that reduces antidepressant usage in advanced AD persons with BPSD.